The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1088/1475-7516/2013/12/001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dark matter and dark energy interactions on the peculiar velocity field and the kinetic Sunyaev-Zel'dovich effect

Abstract: The interaction between Dark Matter and Dark Energy has been proposed as a mechanism to alleviate the coincidence problem. We analyze its effects on the evolution of the gravitational and the peculiar velocity fields. We find that for different model parameters peculiar velocities vary from a factor five times smaller to two times larger than in the ΛCDM cosmological model at the same scales. We propose two new observables sensitive to such interactions based on their effect on the velocity field. We compare t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 86 publications
(154 reference statements)
4
46
0
Order By: Relevance
“…Hence, many different scenarios of interacting dark energy have been constructed (see [7,8] for reviews and references therein). Interestingly enough, recently it has been shown that the current data might favor the late-time interaction between CDM and the vacuum energy [9][10][11][12] or the dynamical dark energy sector [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, many different scenarios of interacting dark energy have been constructed (see [7,8] for reviews and references therein). Interestingly enough, recently it has been shown that the current data might favor the late-time interaction between CDM and the vacuum energy [9][10][11][12] or the dynamical dark energy sector [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…We plot the evolution of the DE fractional energy density in that energy flows from DE to DM [21][22][23][24][25]. For the same amount of DE today, with the positive coupling, it implies that DE density was higher in the past.…”
Section: Analytical Formalismmentioning
confidence: 99%
“…A more natural understanding, in the framework of field theory, 3 is to consider that there is some kind of interaction between them. It has been shown that the interaction between DM and DE is allowed by astronomical observations and can help to alleviate the coincidence problem, see for example [21][22][23][24][25] and references therein. It would be of great interest to extend the previous studies to the interaction between EDE and DM.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy to mention that they obtain slightly negative interaction in some cases. In [31] the authors contrast dark sector interactions with three different observables show a relation between the sign and amplitude of the interaction with the amplitude of the kSZ effect. They also mention that future experiments might provide the first detection of interaction in the dark sector.…”
Section: Introductionmentioning
confidence: 99%